Water-in-Crude Oil Emulsions: Its Stabilization and Demulsification - Nour, A. H.; R. M., Yunus; Anwaruddin, Hisyam (Asian Network for Scientific Information, 2007)
Traditional ways of breaking emulsions using heat and chemicals are disadvantageous from both economic and environmental perspectives. In this research, the potentials of microwave technology in demulsification of water-in-crude oil emulsions are investigated. The study began with some characterization studies to provide understandings of fundamental issues such as formation, formulation and breaking of emulsions by both chemical and microwave approaches. The aim was to obtain optimized operating conditions as well as fundamental understanding of water-in-oil emulsion stability upon which further developments on demulsification processes could be developed. It was found that emulsion stability was related to some parameters such as, the surfactant concentration, water content, temperature and agitation speed. Experimental results found that microwave radiation method can enhance the demulsification of water-in-oil emulsions in a very short time compared to the conventional heating methods. The results obtained in this study have exposed the capability of microwave technology in demulsification of water-in-oil emulsion. Further works are nevertheless required to provide deeper understanding of the mechanisms involved to facilitate the development of an optimum system applicable to the industry.